Strategi Mitigasi Risiko Produksi Usahatani Cabai Rawit Di Kelurahan Malumbi Kecamatan Kambera Kabupaten Sumba Timur - Ngguna, Ardi Konda; Wadu, Junaedin (Sandalwood Journal Of Agribusiness And Agrotechnology, 2025)
Abstrac: This study was conducted in Malumbi Village,Kambera District,East Sumba Regency. The locationwas selected based on the consideration that Malumbi Village, Kambera District is one of the areas thatcultivates cayenne pepper in East Sumba Regency and its production experiences fluctuations that indicate risk.The objectives of this study were 1) to determine the magnitude of production risk and cayenne pepper pricerisk in Malumbi Village with 26 informant sources, and 2) to develop strategies to deal with production risksusing SWOT analysis with Stakeholders. The sampling technique used was simple random sampling. Based onthe results of this study, it shows that the level of production risk and cayenne pepper price risk are 12.75% and7.44%, respectively. Meanwhile, the analysis of internal factors in the study showed that the main strength isthe indicator of the area of land owned by farmers with a value of 1.72 greater than the main weaknessvalue of 1.13, while the main opportunity is 1.55 and the main threat is 0.28. Meanwhile, the priority strategybased on the QSPM analysis is the application of modern cultivation techniques or methods in an effort toincrease farming productivity.Keywords: Coefficient Of Variation, Risk, Strategy, SWOT, QSPM